IMPROVING THE MECHANISM FOR COLLECTING LAND TAX FROM INDIVIDUALS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This thesis was considered to improve the mechanism for charging land taxes from individuals.